2022
DOI: 10.1111/joop.12389
|View full text |Cite
|
Sign up to set email alerts
|

Better to be optimistic, mindful, or both? The interaction between optimism, mindfulness, and task engagement

Abstract: This paper investigates the relationships between optimism, mindfulness, and task engagement. Specifically, we hypothesized that optimism, mindfulness, and their interaction would facilitate individuals' task engagement. We tested our research model in four studies: two surveys among gig workers and two experiments. The results of the two surveys among gig workers indicated that optimism predicted higher task engagement, but trait mindfulness did not, and that a multiplicative interaction existed between high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 153 publications
0
3
0
Order By: Relevance
“…Mindfulness of the modular learning modality Several research has demonstrated how mindfulness can improve cognitive abilities like memory, thinking, problem-solving, and emotional equilibrium. An enhanced attention to and awareness of experience, as it occurs in the present moment, resulted in a stronger desire for the students to finish their tasks (Bunjak, Hafenbrack, Černe, & Arendt, 2022). Additionally, Henriksen, Richardson, and Shack (2020) claimed that the more aware people are of this construct and of their own mind's activities, the more capable they become of noticing and attending to creative ideas in productive ways.…”
Section: Discussionmentioning
confidence: 96%
“…Mindfulness of the modular learning modality Several research has demonstrated how mindfulness can improve cognitive abilities like memory, thinking, problem-solving, and emotional equilibrium. An enhanced attention to and awareness of experience, as it occurs in the present moment, resulted in a stronger desire for the students to finish their tasks (Bunjak, Hafenbrack, Černe, & Arendt, 2022). Additionally, Henriksen, Richardson, and Shack (2020) claimed that the more aware people are of this construct and of their own mind's activities, the more capable they become of noticing and attending to creative ideas in productive ways.…”
Section: Discussionmentioning
confidence: 96%
“…First, drivers' intrinsic motivation plays a dominant role in their work engagement (Hua et al. , 2020) and personal traits, such as optimism, can also promote their engagement by strengthening their orientation toward goal achievement (Bunjak et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have also identified the determinants of drivers' work engagement on online car-hailing platforms. First, drivers' intrinsic motivation plays a dominant role in their work engagement (Hua et al, 2020) and personal traits, such as optimism, can also promote their engagement by strengthening their orientation toward goal achievement (Bunjak et al, 2022). Second, the nature of gig work also affects drivers' work engagement.…”
Section: Work Engagement Of Online Car-hailing Driversmentioning
confidence: 99%